SISTEM INFORMASI E-RAPORT MENGGUNAKAN EXPECTATION CONFIRMATION MODEL (ECM) PADA SMAN 1 PABUARAN - Waliadi Gunawan; Nur Hidayanti; Ramdani Budiman; Anan Bahtiar Rifai (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
SMA Negeri 1 Pabuaran is one of the schools that has implemented the 2013 Curriculum. The change from the KTSP curriculum to the 2013 curriculum certainly changes the value management process. The process of managing report cards carried out is currently less effective and efficient because the process is carried out separately using Microsoft Excel. There is often a difference in the format of report values between subject teachers and homeroom teachers, so homeroom teachers need to change these scores to fit the proper format. The purpose of this study is to design and develop a value management information system using a web-based E-Report and to conduct quality testing using the Expectation Confirmation Model (ECM) method on the information system developed. The system design used in this research is using the Waterfall method so that it is easier to develop and use UML (Unified Modeling Language) for visual system modeling. The results achieved after the implementation of this application make it easier for users (teachers, homeroom teachers, and student parents) to do their work and overcome the difficulties of inputting report values that have been done in schools. The conclusion obtained is that using the e-rapport application can support improvements in work so that the process of inputting values ​​is more effective and efficient. The value of the report becomes more structured and well-documented. The results of the research on the level of user satisfaction with thee-rapport system are in the very good or very satisfied category.